Penyetinggan Loss Of Field Relay Proteksi Generator Pada Pembangkit Listrik Tenaga Air - Samsurizal Samsurizal; Dedi Kurniawan (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2019)
Hydroelectric generators require stability of the voltage generated. When excitation the generator voltage drops will be lower than the terminal voltage so the engine will work on the power factor One disturbance that occurs in synchronous generator is interference with loss of excitation field. This disruption occurs when the generator excitation current is lost due to damage to the excitation system, while the generator is still connected to the electrical grid, causing the reactive power generated by the generator to be reduced or even lost so that the generator will draw reactive power from the electrical network system and act as an induction generator. To release the impact needed by the protection system one of them with the Mho offset release. In this study, using 2 protection zones, namely zone 1 and zone 2. For zone 1, the removal of excitation at a value of 1 pu with a delay time of 0.5 seconds, while for zone 2 the excitation fails occurred at a value of 2,140 pu with a delay time of 2.0 seconds, while the Mho offset value released in zone 1 and zone 2 will work at a value setting of 0.122 pu with a delay time of 0.5 seconds Keywords: Protection,  Synchronous generator, Protection Zone, Excitation